2019
DOI: 10.1051/0004-6361/201834715
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Yarkovsky force on Jupiter Trojan asteroids

Abstract: Aims. We investigate the influence of the Yarkovsky force on the long-term orbital evolution of Jupiter Trojan asteroids. Methods. Clones of the observed population with different sizes and different thermal properties were numerically integrated for 1 Gyr with and without the Yarkovsky effect. The escape rate of these objects from the Trojan region as well as changes in the libration amplitude, eccentricity, and inclination were used as a metric of the strength of the Yarkovsky effect on the Trojan orbits. Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…We first note that the formation of the three small body populations, the MBAs, JTAs, and TNOs have been greatly shaped by the early solar system history (see Nesvorný 2018, for a review) and since then they have been evolving under a quiescent environment for 4 Gyr. As a consequence, the dynamical (Minton & Malhotra 2010;Di Sisto et al 2014;Muñoz-Gutiérrez et al 2019) and collisional (Bottke et al 2005;Hellmich et al 2019;Durda & Stern 2000) erosion over the next several Gyr before the Sun reaches the giant brach will be mild and the majority of mass contained (in large objects) within the three populations will not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…We first note that the formation of the three small body populations, the MBAs, JTAs, and TNOs have been greatly shaped by the early solar system history (see Nesvorný 2018, for a review) and since then they have been evolving under a quiescent environment for 4 Gyr. As a consequence, the dynamical (Minton & Malhotra 2010;Di Sisto et al 2014;Muñoz-Gutiérrez et al 2019) and collisional (Bottke et al 2005;Hellmich et al 2019;Durda & Stern 2000) erosion over the next several Gyr before the Sun reaches the giant brach will be mild and the majority of mass contained (in large objects) within the three populations will not be affected.…”
Section: Discussionmentioning
confidence: 99%
“…This thrust will gradually change the semimajor axis of a body, with the scale and direction of the induced drift dependent on the thermal properties, axis of rotation and size of the object (Brož et al 2005;Bottke et al 2006). In the case of the Jovian Trojans, simulations of hypothetical objects have indicated that at small sizes (<1 km), the Yarkovsky effect could impact the stability of the objects (Wang & Hou 2017;Hellmich et al 2019). As we are simulating known Jovian Trojans, the majority of the objects are greater than several kilometres in size (Emery et al 2015), and have unknown or highly uncertain thermal properties (Slyusarev & Belskaya 2014;Sharkey et al 2019).…”
Section: E T H O D Smentioning
confidence: 99%
“…This is due to the dependence of the Yarkovsky effect on the Solar flux. At the 5.2au mean semi-major axis of the Jovian Trojans, the mean Yarkovsky effect is minimal, particularly for Trojans over 1km in diameter (Wang & Hou 2017;Hellmich et al 2019).…”
Section: Clustering Methodsmentioning
confidence: 96%